ANU GRACE Data Analysis: Characteristics and Benefits of Using Irregularly Shaped Mascons. Issue 2 (23rd February 2022) - Tregoning, P.; McGirr, R.; Pfeffer, J.; Purcell, A.; McQueen, H.; Allgeyer, S.; McClusky, S. C.
Abstract: The estimation of mass anomalies using Gravity Recovery and Climate Experiment (GRACE) data involves parameterizing the temporal gravity field using basis functions. In this study, we show that the use of irregularly shaped mass concentration (mascon) tiles that follow land/ocean boundaries reduces the leakage of land signals into ocean regions and vice versa. Leakage of signal from continents to oceans in mascons that cross the coastline affect the integrated mass changes at a regional scale. For example, the calculated mass loss in 2016 is ∼5% greater for Greenland when using mascons that follow coastlines. We describe efficient algorithms for computing the accelerations acting on the satellites caused by mass changes on mascons, along with the partial derivatives relating the mass changes to the inter‐satellite observations. Through simulation, we quantify the impact of different mascon geometries, spatial resolution and regularization. The variations of mass change signals within mascons, which we call "intra‐mascon variability, " contribute to errors in estimates of mass variation from GRACE data. While this can be mitigated through the regularization of the inversions, it cannot be removed entirely. The use of irregularly shaped mascons that follow land/ocean boundaries reduces the "intra‐mascon leakage" of land signals into ocean regions and vice versa. This approach can also be applied to hydrological basins for calculating integrated mass changes on catchment scales. Plain Language Summary: The changes in the strength of the Earth's gravity field are mostly caused by changes in the distribution of water and ice across the Earth. Recent analysis approaches have divided the surface of the Earth into regularly shaped regions, then estimated the change in mass across each region in terms of the height of a layer of water covering the region. This approach is problematic when the mass change signals vary in magnitude within regions and this variability causes errors in estimates of the signal. A second issue arises when the regions span continent and ocean boundaries, because there may be a very different signal for the continental part compared to the ocean part of the region. This is particularly important in places where significant mass loss is occurring from glaciers and ice sheets adjacent to the coastline and causes the ice loss signal to leak into the ocean. With our new approach our regions follow coastlines, thereby mitigating the problem of signal leakage between continents and oceans. Our approach can also be used to contain signals within hydrological and glacier drainage basins. Key Points: We use an irregular‐shaped mass concentration pattern covering the Earth when estimating the temporal gravity field Our approach permits mascons of varying sizes to be used and mitigates the leakage of signals between oceans and continents Variability of signal magnitude within mascons contributes to errors in gravity field estimates